Thermoelectric properties of nanostructured tetrathiotetracene iodide crystals in a two-dimensional model - Sanduleac, Ionel; Casian, A.I.; Pflaum, Jens (American Scientific Publishers, 2014)
Previously, it has been predicted that nanostructured crystals of tetrathiotetracene iodide are very promising candidates for thermoelectric applications. However, these predictions are based on a strictly one-dimensional (1D) model. In order to verify these conclusions, a two-dimensional (2D) model is elaborated which explicitly takes into account the weak interaction of carriers with the nearest conductive chains. It is shown that for crystals with a rather low degree of purity this interaction does not affect significantly the results obtained by the 1D approximation, but for ultrapure crystals this interaction can no longer be neglected.